2008
DOI: 10.1007/s10800-008-9516-4
|View full text |Cite
|
Sign up to set email alerts
|

Controlled stripping of aluminide coatings on nickel superalloys through electrolytic techniques

Abstract: Aluminide diffusion coatings are widely employed to improve the oxidation and/or the corrosion resistance of highly added value turbine components operating in harsh environments at high temperatures. Refurbishment of such components requires appropriate removal of worn coatings and of the corrosion products layer-usually an oxide scale. Stripping is mostly carried out using hazardous chemical baths of limited reliability. In this work, an alternative stripping method based on electrochemical techniques has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…On the other hand, such a combination of acids should be safe for the surfaces of substrates. Considering the requirements above, many acids and inorganic reagents, such as (NH 4 ) 6 Mo 7 O 24 , HNO 3 , HF and HCl, and their combinations, have been adopted [11][12][13][14]. Poupard et al investigated various soft chemical stripping methods and found that chemical baths containing relatively high concentrations of pitting reagents in organic media are the most effective [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, such a combination of acids should be safe for the surfaces of substrates. Considering the requirements above, many acids and inorganic reagents, such as (NH 4 ) 6 Mo 7 O 24 , HNO 3 , HF and HCl, and their combinations, have been adopted [11][12][13][14]. Poupard et al investigated various soft chemical stripping methods and found that chemical baths containing relatively high concentrations of pitting reagents in organic media are the most effective [15].…”
Section: Introductionmentioning
confidence: 99%
“…TBC removal technique could be roughly divided into two categories: physical removal technologies [16,17], e.g., sandblasting, grinding, polishing, and machining, and chemical removal technologies [18,19], e.g., soft chemical stripping and electrochemical method. TBC is difficult to be completely removed through physical technology due to process characteristics, and strong mechanical impact will exert intense local stress and deformation on metallic components [20,21]. This contradicts the purpose of the refurbished TBC, which is to protect and reuse higher-value metallic components.…”
Section: Introduction mentioning
confidence: 99%
“…Equations (1a) and (1b) show the spontaneous decay of electrons to the ground state from the Ē and 2 Ā states producing the R 1 and R 2 spectral lines characteristic of ruby fluorescence: The repair and overhaul process requires that turbine blades are entirely stripped of their oxidized diffusion coating before a new coating can be deposited [9]. This is achieved by alumina-grit blasting and immersive chemical stripping in hot sulphamic and nitric acid [10]. The effectiveness of the stripping process is currently determined by subjective visual assessments.…”
Section: Introductionmentioning
confidence: 99%